2022
DOI: 10.3390/fermentation8080353
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Agent Chitooligosaccharides Derived from Solid-State Fermentation of Shrimp Shell Waste by Pseudonocardia antitumoralis 18D36-A1

Abstract: Shrimp shell waste is a potential source of the biopolymer chitin. Through fermentation, chitin can be converted into its derivative products. This study aimed to isolate and characterize the products of the biodegradation of chitin from shrimp shell waste through a solid-state fermentation process using actinomycetes. Actinomycete isolates were obtained from tunicate marine biota collected from the waters of Buleleng, Bali, using a dilution technique on 1% chitin colloid agar medium. The isolated actinomycete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The COS sample with the strong presence of chitohexaose showed the highest fungal growth inhibition [88] pathogenic fungi, the studies differ regarding the diluents of these molecules. Some did not even mention this important assay parameter (Table 3).…”
Section: Malassezia Globosamentioning
confidence: 94%
“…The COS sample with the strong presence of chitohexaose showed the highest fungal growth inhibition [88] pathogenic fungi, the studies differ regarding the diluents of these molecules. Some did not even mention this important assay parameter (Table 3).…”
Section: Malassezia Globosamentioning
confidence: 94%
“…11 were the largest and brightest, and it could be preliminarily determined that strain No. 11 had the highest saponin yield [27]. From Figure 3b, using the bar chart to compare the saponin yield after the fermentation of the screened strains, it can be concluded that, among them, the saponin yield of No.…”
Section: Screening Of High Yield Diosgenin Strains By Compound Mutage...mentioning
confidence: 95%
“…However, the same technology has not been yet applied for the optimization of potential biopesticides released by this species (e.g., antifungal chitinases) [177]. Also, the recent work of Widyastuti et al described the Pseudonocardia antitumoralis 18D36-A1 SSF using shrimp shell wastes to produce antifungal biopesticides against Malassezia globose (a mammalian pathogen) [178]. Fusarium oxysporum [196] Streptomyces similanensis 9X166 M rice bran, cassava chips, and coconut husks 33 ± 2 • C 7 151 × 10 7 CFU/g −1 Phytophthora palmivora [197] In the table, Tg, Targets:B, bacteria; M, molds; I, insects; Q, mosquitos; D, SSF days; DM, dry matter.…”
Section: Solid-state Fermentation For Biopesticides Productionmentioning
confidence: 99%
“…However, the same technology has not been yet applied for the optimization of potential biopesticides released by this species (e.g., antifungal chitinases) [ 177 ]. Also, the recent work of Widyastuti et al described the Pseudonocardia antitumoralis 18D36-A1 SSF using shrimp shell wastes to produce antifungal biopesticides against Malassezia globose (a mammalian pathogen) [ 178 ].…”
Section: Solid-state Fermentation For Biopesticides Productionmentioning
confidence: 99%